An improved contribution to optimize Si and GaAs solar cell performances - Merabtine, N.; Amourache, S.; Bouaouina, M.; Zaabat, M.; Saidi, Y.; Kenzai, C. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In resent years a considerable effort (experience, numerical simulation and theoretical prediction models) has been devoted to the study of photovoltaic devices characterised by high efficiency and low cost. The present study comes in way to contribute in the optimisation of the performance of Si an GaAs based (N/P) solar cells by the determination of physical and technological parameters giving the best photovoltaic conversion efficiency and a good spectral response. The four principal parameters that influence the operation of a solar cell are emitter and base doping, junction depth and base thickness. We have also taken into account the recent technique of elaboration of these structures. This study concerns the use of novel optimised values of electronic properties of GaAs and Si materials such as recombination velocity at surface (front and back). All enhancements recently reached: BSF, BSR layers, ARC anti reflection layer with textured surface, surfaces passivation, improved ohmic contacts are taken into account. I-V, P-V, EQE-λ characteristics obtained by PC1D similator on two different cells (Si and GaAs) under the global spectra AM1.5 have allowed us to get optimal cells. The comparison of the cells shows the advantage of given GaAs cells. The effect of solar concentration (1-100 suns) on cell operation has been studied. The later has contributed to the enhancement of the energetic efficiency. The effects different standard spetra such as AM1, AM1, 5G, and AM1.5D have been studied. The optimal values of physical parameters giving the best currents of short-circuit and voltages of open circuit as well as high conversion efficiency have been obtained for these two solar materials.